Optimalisasi Budidaya Tanaman Pangan Ramah Lingkungan Berbasis Teknologi Pertanian Organik - Nofianti Zebua; Nensia Natalia Waruwu; Cahya Masa Indah Zendrato; Faristina Laia; Yoel Melsaro Larosa; Putra Hidayat Telaumbanua (CV. SINAR HOWUHOWU, 2025)
This study aims to evaluate the use of organic farming technology in the cultivation of environmentally friendly food crops. The research method is based on a review of previous studies, using a literature study approach. The data collected came from literature sources, through the process of reading, recording, and managing research materials. The data sources were taken from existing journals or articles and books related to agriculture. The observations focused on plant growth and soil conditions during the planting period, as well as assessing the extent to which organic technology was successfully applied in various regions in Indonesia. The results showed that organic farming provides positive benefits to soil health, such as increasing organic matter content, increasing microbial activity, and improving soil structure. In addition, this agricultural system also has a high economic value because its products can be sold at higher prices, both in domestic and foreign markets. Socially, the implementation of organic farming encourages people to participate in activities such as composting and natural pest management training. Thus, organic farming not only helps keep the environment sustainable, but also strengthens the economic and social resilience of farmers in a sustainable manner.